The Effect of Myo Fascial Release With Red Betel Ginger Oil on Muscle Spasms in The Practice of Indepedent Physiotherapy Marendal - Tuty Swarni Sinaga; Jhon Roby Purba (International Journal of Health Engineering and Technology, 2025)
Background: Muscle spasm is a frequent musculoskeletal problem that can disrupt daily activities, reduce productivity, and decrease quality of life. Ginger (Zingiber officinale) contains bioactive compounds with thermogenic properties that can enhance blood circulation and muscle relaxation, while red betel leaf (Piper crocatum) possesses analgesic and anti-inflammatory effects that may help alleviate musculoskeletal pain. In physiotherapy practice, alternative therapies such as herbal oil rubs and manual techniques like Myofascial Release (MFR) are gaining popularity due to their non-invasive and holistic approach. Objective: This study aimed to determine the effect of combining red ginger and red betel leaf oil rub with MFR in reducing muscle spasm. Methods: This was a pre-experimental study with a one-group pre-test–post-test design. A total of 10 participants (aged 35–55 years; both male and female) with muscle spasm were recruited. Intervention consisted of topical application of red ginger and red betel leaf oil followed by MFR therapy for five consecutive days. Pain intensity was measured using the Visual Analogue Scale (VAS). Data were analyzed using paired sample t-test. Results: There was a significant decrease in VAS scores from a mean of 4.4 pre-treatment to 4.0 post-treatment. Statistical analysis revealed a highly significant difference (p < 0.000000001), indicating that the combined intervention effectively reduced muscle spasm.